EFEKTIVITAS EKSTRAK DAUN KENIKIR (COSMOS CAUDATUS) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PADA TIKUS DIABETIK : TINJAUAN SISTEMATIS LITERATUR - Indriyani Febiya Ningrum (2022)
Introduction : Hypercholestrolemia in Diabetes Melitus (DM) is a disease with a high risk of cardiovascular disease (CVD) and causes the highest mortality rate in Indonesia. Increased insulin resistance in DM can increase fatty acids from adipose tissue into the blood circulation. Increased level of cholesterol in the blood accompanied by DM can cause several complications and can lead to progression if not treated immediately. Cosmos caudatus has a high bioactive flavonoid content and is known to function as antidiabetic, antihypercholesterol and antioxidant. The purpose of this study was to determine the effectiveness of C.caudatus in reducing total cholesterol levels in DM. Methods : A systematic literature review search was conducted on the basis of Pubmed, Sciencedirect, Google scholar, Scopus using the PRISMA-P methode and journal elimination using JBI Critical Appraisal Checklist. Results : There were 9 Journals in good category, with the result that C.caudatus was able to reduce total cholesterol levels, LDL-C, increase HDL-C, and repair pancreatic damage. Conclusion : C.caudatus is effectice in lowering total cholesterol levels